News In Levels website to sharpen students’ critical thinking: Student’s Perspective - Hanifah Azhari; Robiatul Adawiyah; Eliasanti Agustina (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the explorer of News in Levels as a learning medium in enhancing reading skills and critical thinking among fifth-semester students of the English Education Program at Universitas of Indonesia. News in Levels is an online news platform that presents current events in three levels of English proficiency, allowing students to engage with content suited to their language ability. The platform not only supports literal comprehension but also encourages students to analyze information, construct arguments, and compare news across levels—core components of critical thinking. The research employed a qualitative descriptive approach, with data collected through interviews involving three students who actively use News in Levels in their learning process. The interviews focused on students’ perceptions of how the platform helps them understand texts more deeply, identify main ideas, draw conclusions, and respond to current issues reflectively and critically. Findings indicate that News in Levels assists students not only in understanding English texts but also in developing analytical thinking about news content. All three participants reported that reading news across different levels enabled them to build layered comprehension, which eventually led to deeper analysis. The platform’s audio features and simple yet informative structure made it easier for students to identify the writer’s perspective and form their own opinions based on the information read. Thus, News in Levels proves to be an effective learning medium for improving not only reading skills but also critical thinking abilities, particularly in the context of English as a foreign language learning.